2017
DOI: 10.1007/s40120-017-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IC Study Evaluating the Safety, Tolerability, Pharmacokinetics, and Cognitive Outcomes of BI 409306 in Patients with Mild-to-Moderate Schizophrenia

Abstract: IntroductionThis randomized, double-blind, parallel-group study investigated the safety, tolerability, pharmacokinetics (PK), and cognitive outcomes of BI 409306—a selective phosphodiesterase 9A (PDE9A) inhibitor—in patients with schizophrenia.MethodsPatients with mild-to-moderate schizophrenia were randomized (1:1:1:1) to receive BI 409306 at 25, 50, or 100 mg or placebo once daily over 14 days. The primary endpoints were safety and tolerability; the secondary endpoints were PK and cognitive outcomes.ResultsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
1
3
1
Order By: Relevance
“…as secondary endpoints, no significant treatment effects of BI 409306 on cognitive outcomes were observed in 38 patients with schizophrenia (Brown et al, 2018). Overall, the observed effects of BI 409306 on cognition in patients contrast with the effects in rodents reported in the present study.…”
Section: Downloaded Fromcontrasting
confidence: 81%
See 1 more Smart Citation
“…as secondary endpoints, no significant treatment effects of BI 409306 on cognitive outcomes were observed in 38 patients with schizophrenia (Brown et al, 2018). Overall, the observed effects of BI 409306 on cognition in patients contrast with the effects in rodents reported in the present study.…”
Section: Downloaded Fromcontrasting
confidence: 81%
“…In the first-in-human study, BI 409306 demonstrated good safety and tolerability following the administration of single rising doses up to 350 mg in healthy male participants, and BI 409306 was rapidly absorbed and eliminated (Moschetti et al, 2016). BI 409306 was also well tolerated over 14 days of daily treatment in healthy individuals (Moschetti et al, 2018) and in patients with schizophrenia (Brown et al, 2018). However, to fully assess the efficacy of BI 409306 in human patients, translatable biomarkers are required that provide similar objective measures of drug outcomes in patients, healthy volunteers, and animal models.…”
Section: Discussionmentioning
confidence: 98%
“…These preclinical data lend additional support to the rationale for the ongoing Phase II trial of BI 409306 as an add-on therapy for the prevention of relapse in adult patients with schizophrenia (NCT03351244). In the present study, the observed plasma exposure of BI 409306 1 mg/kg was in the range that would be expected for human participants after a 50 mg dose, based on exposure levels observed in previous clinical studies in healthy volunteers and patients with schizophrenia [7,8,29]. This dose is used in the ongoing clinical trials on prevention of relapse in schizophrenia [10] and early intervention in patients with APS [35], further supporting the relevance of our findings to patients.…”
Section: Discussionsupporting
confidence: 88%
“…Based on the potency of BI 409306 against the PDE9 enzyme and a CSF/plasma ratio of 0.2 [7], this plasma exposure corresponds to a CSF exposure similar to the BI 409306 half maximal inhibitory concentration (IC 50 ) against PDE9. Furthermore, this plasma exposure was in the range reported in clinical studies in healthy male volunteers and in patients with schizophrenia after a single oral dose of BI 409306 25 mg [8,29]. Study 1: BI 409306 dose-response study in adult offspring In the social interaction test, MIA offspring did not display a clear preference toward the live mouse, as indicated by a main effect of prenatal poly(I:C) treatment in the two-way ANOVA (F[1,48] = 7.332; P = 0.009; Supplementary Fig.…”
Section: Pharmacokinetic Study and Plasma Exposurementioning
confidence: 52%
See 1 more Smart Citation